Metals in Feathers of African Penguins (Spheniscus demersus): Considerations for the Welfare and Management of Seabirds Under Human Care - Squadrone, S.; Abete, M. C.; Brizio, P.; Pessani, D.; Favaro, L. (Bulletin of Environmental Contamination and Toxicology, 2018)
Bird feathers have been proven to be reliable indicators of metal exposure originating from contaminated food and polluted environments. The concentrations of 15 essential and non-essential metals were investigated in African penguins (Spheniscus demersus) feathers from a Northwestern Italian zoological facility. These birds are exclusively fed with herring from the northeast Atlantic Ocean. Certain elements, such as Hg and Cd, reflected the bioaccumulation phenomena that occur through the marine food chain. The levels of Cr, Mn, and Ni were comparable to those registered in feathers of birds living in polluted areas. These results are important for comparative studies regarding the health, nutrition and welfare of endangered seabirds kept under human care.